Managerial Performance in Village Government: Does Transformational Leadership Matters? - Rahmawati, Evi; Kholid, Arif Wahyu Nur; Adiyatama, Evan Ardis; Sofyani, Hafiez (Jurnal Dinamika Akuntansi dan Bisnis, 2024)
This study examines the transformational leadership moderating role on the relationship between public accountability and budget participation on managerial performance in Indonesian village governments. The population of this study is the village apparatuses of the village government in Bantul Regency. The samples were selected using convenience sampling technique and data were collected through questionnaires. Hypotheses testing was conducted by utilizing Structural Equation Modelling-Partial Leas Square (SEM-PLS) method. The results unveiled that transformational leadership has a quasi-moderation role. Transformational leadership can reinforce the effect of budget participation on managerial performance while public accountability cannot affect managerial performance. It reveals that public accountability cannot promote and motivate the village apparatus to enhance their performance.